Increasing MIMO capacity in ultra-wideband communications through orthogonal polarizations - Malik, W; Mtumbuka, M; Edwards, D; Stevens, C; IEEE (2005)
This paper assesses the performance of polarization MIMO in an indoor ultra-wideband communications system using measured channel data. The orthogonality of the polarization subchannels is established through correlation analysis and eigenvalue decomposition. The performance advantage is quantified in terms of the gain in Shannon capacity and is compared with narrowband and unipolar systems. It is shown that the fading correlation of the polarized subchannels is lower than 0.3, and the system can achieve spectral efficiencies as high as 17.5 b/s/Hz, providing a channel capacity of over 130 Gbps on a full-band dual-polar UWB system. © 2005 IEEE.